P025 Expert Opinions to Develop a Sleep Intervention for Patients with Low Back Pain: A Nominal Group Study. (7th October 2021) - Comis, J; Hodges, P; Gordon, C; Ho, K; Ferreira, P
Abstract: Introduction: Insomnia is a common comorbidity of low back pain. Research has investigated the use of cognitive behavioural therapy interventions for insomnia (CBT-I) to treat these conditions but show little effect on improving pain outcomes. This study sought the opinion of experts to explore how existing online CBT-I interventions could be optimised to improve sleep and pain outcomes in patients with comorbid insomnia and LBP. Methods: This study was conducted using the nominal group technique, a structured meeting to generate ideas and rank priorities amongst a panel of experts. Musculoskeletal researchers (n=7) and clinicians (n=1), sleep researchers (n=2), and a consumer advocate (n=1) were purposively sampled to participate in a 2-hour online nominal group workshop. A quantitative analysis was conducted to rank ideas by their relative importance. A qualitative analysis was used to provide context on the highest ranked ideas. Results: A total of 58 ideas were generated and subdivided into 11 primary categories, each of which contained a varying number of sub-ideas. The primary categories, personalisation of care, assessment guided management, understanding the user experience, personalised advice on physical and environmental factors, and continual re-assessment to guide management, were ranked one to five respectively and accounted for 73% of all votes from the panel. Discussion: An intervention framework consisting of three interacting domains, personalisation of the intervention, assessment guided management, and user experience was proposed. This framework outlines recommendations that should be considered to improve online CBT-I interventions to treat patients with comorbid insomnia and low back pain.